IMPROVING STUDENTS’ SPEAKING SKILL IN EXPRESSING OFFERING BY USING ROLE PLAY TECHNIQUE - Asramadhani -; Sri Minda Murni (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
AbstractThis research concerns on improving students’ speaking skill in expressingoffering by using role play technique. The objective was to find out theimprovement of students’ speaking skill in expressing offering. This research wasconducted by using action research method. The subject of the research was Xcstudents of SMA Negeri 1 Stabat. The numbers of students were thirty sixstudents. They were taught speaking skill in expressing offering by using role playtechnique. The instruments used were the examples of conversation, diary notes,interview sheets, questionnare and observation sheets. In analyzing data, the meanof students’ score for the first competency test was 59,5, for the secondcompetency test was 69,4 and for the third competency test was 77,7. Theconclusion is that by using role play technique can improve the students’ speakingskill in expressing offering. It is suggested that teachers to use role play as one ofstrategy to improve students’ speaking skill in expressing offering.Key words: Speaking Skill, Expressing Offering, Role Play Technique